III-nitride : semiconductor materials - Feng, Zhe Chuan (Imperial College Press ; Distributed by World Scientific, 2006)
III-Nitride semiconductor materials - (Al, In, Ga)N - are excellent wide band gap semiconductors very suitable for modern electronic and optoelectronic applications. Remarkable breakthroughs have been achieved recently, and current knowledge and data published have to be modified and upgraded. This book presents the new developments and achievements in the field. Written by renowned experts, the review chapters in this book cover the most important topics and achievements in recent years, discuss progress made by different groups, and suggest future directions. Each chapter also describes the basis of theory or experiment. The III-Nitride-based industry is building up and new economic developments from these materials are promising. It is expected that III-Nitride-based LEDs may replace traditional light bulbs to realize a revolution in lighting. This book is a valuable source of information for engineers, scientists and students working towards such goals.